Selected issues concerning expert witness and specialists in Polish penal proceedings and forensic science - Cieśla, Rafał (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The article aims at presenting general characteristics of two subjects in the proceedings, i.e. an expert witness and a specialist. Both institutions are discussed in terms of theory and practice of Polish penal proceedings and forensic science. The issues are especially important in view of the amendments to the Polish Code of Penal Procedure of 1997 concerning the institution of a specialist and the amendments of 2015 concerning an expert witness’s opinion. It should be emphasised that in the course of the proceedings to take evidence, including technical examination of documents, cooperation between an expert witness as its author and a specialist as an assistant may in many cases be necessary or even indispensable.
Keywords: biegły sądowy; specjalista; kodeks postępowania karnego; kryminalistyka; techniczne badanie dokumentów